Novel subgenotype D11 of hepatitis B virus in NaPo County, Guangxi, bordering Vietnam. (16th April 2019) - Ren, Chuang-Chuang; Chen, Qin-Yan; Wang, Xue-Yan; Harrison, Tim J.; Yang, Qing-Li; Hu, Li-Ping; Liu, Hua-Bing; He, Xiang; Jia, Hui-Hua; Fang, Zhong-Liao
Abstract : Hepatitis B virus has been classified into 10 genotypes and 48 subgenotypes worldwide. We found previously, through polymerase chain reaction (PCR) amplification of a sample collected in 2011, that an HBsAg carrier was infected with two genotypes (B and D) of HBV. We carried out cloning, sequencing and phylogenetic analysis of the complete genomes and, for confirmation, analysed a sample collected from the same individual in 2018. Fifteen complete sequences were obtained from each sample. The carrier was infected in 2011 by genotypes B and D and by various recombinants, but only genotype D was present in 2018. The major and minor parents of the recombinants are genotypes B and D, respectively, although the recombination breakpoints vary among them. All 23 genotype D isolates form a cluster, branching out from other subgenotype D sequences and supported by a 100 % bootstrap value. Based on complete genome sequences, almost all of the estimated intragroup nucleotide divergence values between our isolates and HBV subgenotypes D1–D10 exceed 4 %. Compared to the other subgenotypes (D1–D10), 35 unique amino acids were present in our isolates. Our data provide evidence for a novel subgenotype, provisionally designated HBV subgenotype D11.